«Lumen Gentium»: event, text, reception and current questions - Molina, SJ, Diego M. (Razón y fe, 2018)
There can be no doubt about the theological richness of the constitution Lumen Gentium, or its difficult reception. Through this constitution, the Church now stands in a very different manner from how it has been standing in the 20th Century. At the same time, the Church is taken to mean People of God, Temple of communion or Body of Christ; always on the way to its perfect consummation. The difficult reception of the Lumen Gentium is due, on one hand, to the variety and richness of the set as a whole of each note and, on the other hand, to the limited pastoral and evangelizing fruits achieved thus far from this constitution.